Peginterferon Treatment In Children: A Review Of Chronic Hepatitis B And Chronic Hepatitis C Treatment - Makbule EREN (Journal of Pediatric Sciences, 2009)
Despite of extensive blood product screening and national immunization programs, chronic hepatitis B and C infections continues to be a global problem with high mortality, morbidity and economic impact. Even though acquisition of these infections mostly occurs in childhood, major problems appear in adulthood. Cirrhosis and HCC are two major expected late events related to chronic hepatitis B and C infections. Rarely, children may also face these complications. To avoid these complications and increase the life expectancy in adults treatment of these two type infections should be started in childhood with appropriate patient selection. In contrast to children, adults are luckier in terms of treatment alternatives. They have the chance to use more potent antivirals with higher genetic barrier and pegylated form of interferons. Recently, the use of pegylated interferon and ribavirin combinations has been approved in children in Chronic HCV infection. However, chronic hepatitis B treatment in children is still dependent on the use of one type antiviral drug and conventional interferon. Treatment in early ages with an antiviral agent that has limited genetic barrier may block the chance of treatment or reduce the response rate in adulthood in chronic hepatitis B infection. This burden indicates the necessity of new therapeutic modalities in children. In this term pegylated interferons may be one of the optiones. In this article we aimed to reviewe the efficacy and safety of conventional and pegylated interferons, for the treatment of Hepatitis C and B infections in children.